2014
DOI: 10.2174/1381612820666140613120212
|View full text |Cite
|
Sign up to set email alerts
|

PET Radioligands for In Vivo Visualization of Neuroinflammation

Abstract: Neuroinflammation is a well-orchestrated, dynamic, multicellular process playing a major role in neurodegenerative disorders. The microglia which make up the innate immune system of the central nervous system are key cellular mediators of neuroinflammatory processes. In normal condition they exert a protective function, providing tissue repair by releasing anti-inflammatory cytokines and neurotrophic factors. Upon neuronal injury or infection, they become overactivated, thereby releasing neurotoxic substances,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 228 publications
(226 reference statements)
0
54
0
Order By: Relevance
“…Although both [ 18 F]GE-180 and [ 18 F]PBR06 have ~10-fold higher affinity (i.e., K i < 1 nM)33 for TSPO compared to PK11195 ( K i = 9nM), results from our studies demonstrate that [ 18 F]GE-180 is significantly more sensitive than [ 18 F]PBR06 at detecting changes in TSPO density and activated microglia in APP L/S mice. That is, [ 18 F]GE-180 was able to detect increased microglial activation in APP L/S mice aged 8.5-10 months with greater than 2-fold higher sensitivity compared to [ 18 F]PBR06 (cortex: 12.7% genotype difference for [ 18 F]PBR06 versus 26.0% for [ 18 F]GE-180, hippocampus: 8.8% genotype difference for [ 18 F]PBR06 versus 19.5% for [ 18 F]GE-180).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although both [ 18 F]GE-180 and [ 18 F]PBR06 have ~10-fold higher affinity (i.e., K i < 1 nM)33 for TSPO compared to PK11195 ( K i = 9nM), results from our studies demonstrate that [ 18 F]GE-180 is significantly more sensitive than [ 18 F]PBR06 at detecting changes in TSPO density and activated microglia in APP L/S mice. That is, [ 18 F]GE-180 was able to detect increased microglial activation in APP L/S mice aged 8.5-10 months with greater than 2-fold higher sensitivity compared to [ 18 F]PBR06 (cortex: 12.7% genotype difference for [ 18 F]PBR06 versus 26.0% for [ 18 F]GE-180, hippocampus: 8.8% genotype difference for [ 18 F]PBR06 versus 19.5% for [ 18 F]GE-180).…”
Section: Discussionmentioning
confidence: 59%
“…Recent studies directly comparing [ 18 F]GE-180 with [ 11 C]PK11195 in a rat model of stroke 31 and lipopolysaccharide (LPS)-induced acute neuroinflammation demonstrated that [ 18 F]GE-180 has a 1.5-fold higher signal-to-background ratio compared to [ 11 C]PK11195 and a significantly higher binding potential (BP in vivo = 0.92 ± 0.07 versus 0.47 ± 0.06) for detecting microglial activation 32. Since [ 18 F]GE-180 has a higher TSPO affinity compared to [ 11 C]PK11195 ( K i = 9 nM), [ 11 C]DPA-713 ( K i = 4.7 nM), [ 18 F]DPA-714 ( K i = 7 nM), and [ 11 C]PBR28 (5-6 fold higher than PK11195 - i.e., K i ~ 1.5 nM) 33, it has the potential to afford images with higher binding signal. Additionally, [ 18 F]GE-180 belongs to a structurally distinct class of tricyclic compounds (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the only way to analyze 1227 microglial activation in vivo in humans is by PET. The different PET 1228 radioligands for the evaluation of neuroinflammation developed in 1229 recent years target COX2, metalloproteinases and a variety of cell 1230 surface receptors (for review Ory et al, 2014). [ 11 C]-PK11195 is a 1231 labeled form of a ligand of the benzodiazepine receptor whose 1232 expression in microglia is correlated with the degree of damage in 1233 neuroinflammation (Maeda et al, 2007).…”
Section: Q5mentioning
confidence: 99%
“…Positron emission tomography relies on radioligands, which bind to a specific receptor or mimic a biological molecule of interest, and can be used in in vivo studies of neuroinflammation (80). Translocator protein (TSPO) is a 18 kDa mitochondrial membrane protein involved in steroid biosynthesis and is by far the most studied target to quantify microglial activation following TBI (81, 82).…”
Section: Imaging Techniques To Measure the Neuroinflammatory Responsementioning
confidence: 99%